A unifying approach to impersonality in Russian - Schlund, Katrin (Zeitschrift für Slawistik, 2018)
Despite the ever-growing number of studies about impersonal constructions, there is still no unanimity about which constructions actually fall under the label of impersonality. Consensus on how to define impersonals, even within one language, remains elusive in part because of the opposition between formal (subject-centred) and functional (agent-centred) approaches to impersonality, as outlined by Siewierska (2008). The paper attempts to combine both lines of reasoning. It suggests that the impersonal domain in Russian is represented by a network of constructions that are all related to one another by the formal marker of impersonality on the verb (i. e., third person singular neuter) and by semantic and pragmatic characteristics (namely, deviation from prototypical subject properties; Malchukov & Ogawa 2011).
Online veröffentlicht: 23. März 2018
Gesehen am 15.10.2025 (nur Inhaltsverzeichnis)